Could the Lung Be a Gateway for Amphotericin B to Attack the Army of Fungi? - Beatriz Ferreira de Carvalho Patricio; Juliana Oliveira da Silva Lopes Pereira; Michelle Alvares Sarcinelli; Bianca Portugal Tavares de Moraes; Helvécio Vinicius Antunes Rocha; Cassiano Felippe Gonçalves- (MDPI AG, 2022)
Fungal diseases are a significant cause of morbidity and mortality worldwide, primarily affecting immunocompromised patients. Aspergillus, Pneumocystis, and Cryptococcus are opportunistic fungi and may cause severe lung disease. They can develop mechanisms to evade the host immune system and colonize or cause lung disease. Current fungal infection treatments constitute a few classes of antifungal drugs with significant fungi resistance development. Amphotericin B (AmB) has a broad-spectrum antifungal effect with a low incidence of resistance. However, AmB is a highly lipophilic antifungal with low solubility and permeability and is unstable in light, heat, and oxygen. Due to the difficulty of achieving adequate concentrations of AmB in the lung by intravenous administration and seeking to minimize adverse effects, nebulized AmB has been used. The pulmonary pathway has advantages such as its rapid onset of action, low metabolic activity at the site of action, ability to avoid first-pass hepatic metabolism, lower risk of adverse effects, and thin thickness of the alveolar epithelium. This paper presented different strategies for pulmonary AmB delivery, detailing the potential of nanoformulation and hoping to foster research in the field. Our finds indicate that despite an optimistic scenario for the pulmonary formulation of AmB based on the encouraging results discussed here, there is still no product registration on the FDA nor any clinical trial undergoing ClinicalTrial.gov.